PEMILIHAN KODE TUTUR DALAM INTERAKSI SOSIAL PADA SANTRI PUTRI ASRAMA AL-AISYAH PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Aini Nurhayati; Risqi Maulidatul Hasanah (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this research is motivated by the choice of speech codes used in the social interaction of the language of students in different Islamic boarding schools. This research method uses a qualitative approach to the type of field research. This research studies intensively the background of the actual situation and the interaction of the social environment of the Blokagung Banyuwangi female students. The techniques used in collecting data are observation, listening to engagement, taking notes, and documentary studies. The data analysis technique uses a qualitative descriptive technique. The results showed that the selection of speech codes or language choices contained in Al-Aisyah Dormitory included 1) Mixed code totaling 24 data, 2) Code switching totaling 16 data, and 3) Single code or single language totaling 10 data. The factors that influence the choice of speech code include: Participants, Settings, Ends, Relationships between Speakers and Speech Partners, and the Main Points of Conversation.